2021
DOI: 10.3390/app11073040
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties of a Hybrid Biomaterial (PVA/Chitosan) Reinforced with Conductive Fillers

Abstract: In this study, a novel hybrid material based on Polyvinyl Alcohol-Chitosan (PVA-Chi) was made, reinforced with conductive fillers such as the polypyrrole (PPy), Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT: PSS), carbon black (CB), and multi-wall carbon nanotube (MWCNT). In order to observe the mechanical and electrical responses of this composite material, for obtaining composite materials, and to characterize them for the development of applications in engineering, FTIR analysis made clear … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Moreover, the peak at 892 cm −1 was ascribed to the vibration of the C=S bond. [30][31][32] We can observe that in the curve a in Fig. 3D, there are three characteristic peaks at 1351 cm −1 , 1582 cm −1 , and 2699 cm −1 , which are assigned to the D, G, and 2D peaks of the carbon paper, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the peak at 892 cm −1 was ascribed to the vibration of the C=S bond. [30][31][32] We can observe that in the curve a in Fig. 3D, there are three characteristic peaks at 1351 cm −1 , 1582 cm −1 , and 2699 cm −1 , which are assigned to the D, G, and 2D peaks of the carbon paper, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…One of the most interesting results in these studies concerned the interaction between CH and PVA. Olarte‐Paredes et al ( 2021 ) reported that CH improves the mechanical properties of PVA; indeed, it increases its Young's modulus. These results were concordant with our findings, with this explanation that the best mechanical properties were observed in the CH/PVA 25:75 wt%, as reflected in the egg internal quality parameters.…”
Section: Resultsmentioning
confidence: 99%
“…SEM images of blended coatings demonstrated a lower porosity surface morphology at CH/PVA as compared to others. One of the most likely reasons for these results may be that PVA/CH material has synergistic properties and there is good adhesion between the PVA/CH materials (Olarte‐Paredes et al, 2021 ). However, when the CH proportion is increased, it appears slightly as rough areas, due to the CH molecules disrupting the compact structure of the PVA coating (Liu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Many studies have been conducted in order to overcome PANI's solubility in water and degradation rate by using polyvinyl alcohol (PVA) to create a stable PANI dispersion. 18 PVA, in instance, has high mechanical strength and chemical endurance, making it a popular choice to be used as additive. 19 PVA also has a wide spectrum of uses due to its has a carbon chain, which is expected to be a powerful source of bonds formation.…”
mentioning
confidence: 99%